Crystallographic benchmarking of powder X-ray line diffraction pattern profiling of monoclinic sucrose nanocrystal - Md. Khalid Hossain Shishir; Md. Mynul Islam; Md. Tarikul Islam; Md. Ashikur Rahaman; Md. Hasnain Mustak; Md. Golam Mostafa; Md. Ashraful Alam (Results in Surfaces and Interfaces, 2025)
The structural and geometrical properties of sucrose were examined using powder X-ray diffraction (XRD). XRD analysis provided insights into the atomic orientation and enabled precise refinement of lattice parameters and crystal symmetry. Rietveld refinement confirmed a 100 % crystalline sucrose phase, as identified through Whole Powder Pattern Fitting. The calculated lattice parameters were a= 10.844 Å, b= 8.749 Å, c= 7.837 Å, with angles α=γ= 90.0° and β= 102.82°, indicating a monoclinic crystal system. The lattice volume was 724.961 Å3, and lattice strain was 0.138 %. The most intense diffraction peak was observed at 2θ= 20.79°, corresponding to the (21-1) plane. Crystallite size, calculated via the Scherrer equation, was 97.23 nm, confirming the nanocrystalline nature of sucrose. Additional analysis revealed microstrain of 0.00028, dislocation density of 1.058 × 10−4 nm−2, specific surface area of 38.86 m2/g, calculated density of 1.588 g/cm3 and crystallinity degree of 72.99 %. Scanning Electron Microscopy showed sucrose crystals with sharp, angular edges and smooth facets, typical features of crystalline materials. Transmission Electron Microscopy revealed spherical particles with uniform contrast and clear boundaries, averaging 188.58 nm in size. The melting point of sucrose was recorded at approximately 181 °C. This study provides a detailed characterization of sucrose nanocrystals, emphasizing their crystallographic properties, lattice structure and nanoscale morphology using the XRD technique.